Quint and Dirk's Hero Quest - Brallier, Max; Holgate, Douglas (New York : Viking, 2022)
Starring in their own epic adventure, dynamic duo Quint Baker and Dirk Savage encounter new monsters and embark on a post-apocalyptic quest for the ages.
Keywords: Monsters -- Juvenile fiction; Survival -- Juvenile fiction; Zombies -- Juvenile fiction; Monsters -- Fiction; Survival -- Fiction; Zombies -- Juvenile fiction; Fantasy; Humorous stories; Horror stories; Fantasy fiction; Humorous fiction; Horror fiction